PENGARUH CARENT RATIO, NET PROFIT MARGIN, DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PERUSAHAAN MENGGUNAKAN METODE ALTMAN SEKTOR PERDAGANGAN, JASA DAN INVESTASI PADA BURSA EFEK INDONESIA - Desmon Desmon; Andi Surya; Hero Desyantama (Jurnal Manajemen dan Bisnis (JMB), 2022)
AbstractThis study aims to determine the effect of Curent Ratio, Net Profit Margin, Debt to Equity Ratio both simultaneously and partially on the Financial Distress of Service, Trade and Investment companies. The data obtained by the authors for this study were obtained from the Indonesia Stock Exchange, namely the annual financial statements of Services, Trade and Investment companies in 2019 with 36 companies. This study uses a descriptive method with a quantitative approach. The data were analyzed using the Multiple Linear Regression Model approach. Based on the results of data analysis, the regression model was obtained, namely Y= 4,310 + 0,446X1 - 0,062X2 - 0,632X3 + e. The coefficient of determination (R2) = 0.474 or 47.4% variation in the financial distress variable can be explained by variations in the Current ratio, Net profit margin and Debt equity ratio variables, while the remaining 52.8 5 is caused by external factors not included in the model. Based on the F test, the value of Fcount Ftable (11.527 3.28) with a significance of 0.000 0.05, the Ho hypothesis is rejected and the Ha hypothesis accepts, so it can be concluded that the independent variables current ratio (CR), net profit margin (NPM) and debt equity ratio (DER) has a significant effect on the dependent variable financial distress. it can be concluded that the current ratio (CR) variable has a significant effect on the company's financial distress. Variable net profit margin (NPM) obtained a value of t-count t-table (0.671 2.032) with a significance value of 0.507 0.05, it can be concluded that the variable net profit margin (NPM) has no significant effect on the company's financial distress. The debt to equity ratio (DER) variable obtained t-count t-table (3.572 2.032) with a significance value of 0.001 0.05, it can be concluded that the debt to equity ratio (DER) variable has a significant effect on the company's financial distress.Keywords: Financial Distress, Current Ratio, Net Profit Margin, Debt Equity Ratio.